Classroom participation patterns: a case study of Malaysian undergraduate students - Mustapha, Siti Maziha; Nik Abdul Rahman , Nik Suryani (Association of Indonesian Scholars of History Education (ASPENSI), 2011)
This study aims to document undergraduate students’ patterns of participation in Malaysian classrooms. Interviews and observation were carried out. Around 85 students from two communication classes were observed over the period of two semesters (28 weeks). Most of the participants fell between the age of 18-19 years old (65.8%) and 66.7% of the participants were female, while 33.3% were male. Around 24 students from the two classes were interviewed. Four basic patterns of participation emerged from the data; (1) active participation, (2) selective participation, (3) minimal participation, and passive participation. It was also found that students’ individual participation pattern could be influenced a myriad of factors, thus making their participation patterns flexible. This research demonstrated that the participatory roles students took in class could move along the participation continuum; from the most active to the least active. Recommendations are offered to promote students’ participation in the context of higher learning. Educators need to strive towards providing a more supportive, non-threatening, and open learning environment where students would feel comfortable in letting their voice be heard while knowing when to be quiet so they reap benefits from both behaviours.